Channel estimation for MIMO SC-FDE systems via time-domain based approaches - LI Dan-ping; LIU Yi; ZHANG Hai-lin (Tongxin xuebao)
Circularly orthogonal sequences were designed for the time-domain channel estimation in MIMO SC-FDE systems.Firstly,Chu sequences were chosen as the base sequences,which were added by cyclic prefix and cyclic postfix to construct circularly orthogonal training sequences.The channel impulse response can be estimated by calculating the cross-correlation between the received signal and the corresponding local sequence.Further,a new training sequence structure was presented,in which the original "long" training sequences were replaced by successive and identical "short" sequences.The corresponding estimation algorithm achieves the same performance as "long" sequences based method.Simulation results show that the proposed algorithms can offer good BER performance even at low SNR,due to the successful interference suppression between the antennas and the decrease in the noise variance.